Legal Protection Against Child Labor As Employers Mine Excavations - Minan, Minan (Journal of Law, Politic and Humanities, 2024)
Child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity, as well as receive protection from violence and discrimination. The aim of this research is to determine the penalties for mining entrepreneurs who employ minors and to determine the form of legal protection for minors mining workers. This research is normative legal research with a statutory approach. The types of legal materials used are primary, secondary and tertiary book materials. The research results show that the punishment for mining entrepreneurs who employ minors based on Minister of Manpower Regulation 01/MEN/1987 is punishable by imprisonment for a maximum of three months or a fine of up to Rp. 100,000,- (one hundred thousand rupiah). Forms of legal protection for minor mining workers include: protection of working and rest hours, wage guarantees and social security for occupational safety and health, as well as fair and humane treatment. Protection for child workers in the formal sector is regulated by the Minister of Manpower in his regulation no. Per.01/Men/1987 and its implementing regulations, namely: a) Entrepreneurs are required to report mandatory reporting procedures and forms regulated by the Minister of Manpower; b) For labor inspection employees, when carrying out inspections, they should pay special attention to the protection of child workers, and intensify reporting of the results of analyzing and evaluating inspections. Judging from the form of sanctions, the amount of sanctions in the form of monetary fines should not be stated because the value of money is always changing. A monetary fine of Rp. 100,000,- is not commensurate with a prison sentence of three months nowadays. As an option, a monetary fine equal to the entrepreneur's living costs for three months can be stated.